Exploring revisit intention behaviour among tourists: empirical evidence from United Arab Emirates tourism industry / Abdul Raheem Jasim Mohammed - Jasim Mohammed, Abdul Raheem (2014)
Tourism has become such an important sector of the economy that the Department of Tourism and Commerce (DTCM) of the United Arab Emirates (UAE) taking the lead to spearhead the promotion of the UAE as an attractive, competitive and memorable tourist destination. The total tourist experience which refers to a multi-faceted exposure during a tourist’s actual visitation to the UAE is argued to be a strong predictor of his or her revisit intention. As tourism image of the UAE is formed from different sources, it is plausible to suggest that a tourist is most likely to form a more complex image of the UAE as a result of either favourable or unfavourable experience. It goes without saying total tourist experience, the tourism image and tourist responses in respect to their satisfaction, commitment and loyalty is instrumental to their propensity to indulge themselves in word-of-mouth recommendation to their friends and relatives. What is more important is their behavioural intention specifically, their revisit intention which is best nurtured during their vacation in the UAE. This study is therefore empirically examining the antecedents of revisit intention within the context of total tourists experience, tourism images and tourist responses. It is structured according to a quantitative investigation on tourists who checked-in to a hotel and who stayed for a minimum of 3 days. Fifteen International hotels located at three Emirates namely Dubai, Abu Dhabi and Fujairah were chosen for data collection. With 413 respondents the data analyses were conducted by a process of multivariate analysis using structural equation modelling (SEM) via AMOS (Analysis of Moment Structures) software package Version 18.0 Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were performed to validate the scales. Three measurement models and an overall measurement model were generated and tested in compliance with a stringent purification process for the models. The results of the structural modelling provide evidence that core product, tourist commitment and tourist loyalty are significantly related to revisit intention whereas tourist commitment and core product are two important predictors of tourist loyalty. Core product is a strong proxy for tourist satisfaction and tourist commitment. Hence, core product emerged as the most influential experiential element that players should be very concerned with. In addition, environmental turbulence was found to moderate the relationship between tourist loyalties and revisit intention.